Perceptions about caesarean section among women and health care providers: a qualitative study in a rural maternity hospital in Karnataka, India - Attokaran, Teny; Joseph, Merlyn; B., Ramya; D’souza, Caroline Pretista; ., Soumya; Mathew, Maria Mary; Kumari, Rathna; Johnson, Avita Rose (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Caesarean section is life-saving, but rising rates are a cause for concern. Perceptions surrounding caesarean delivery may play a significant role in the shared-decision making process. Objective of this study was to explore the perceptions of caesarean section among antenatal, postnatal women and healthcare providers in a rural maternity hospital in Ramanagara district, Karnataka. Methods: Qualitative research methodology was adopted to explore perceptions regarding preferred birthing mode, caesarean and its perceived complications. Focus group discussions and in-depth interviews were conducted with antenatal and postnatal women, their caregivers and health care providers. Inductive coding approach and thematic framework analysis was done. Results: Five major themes emerged regarding perceptions of caesarean section among women in a rural area of Karnataka: understanding, fears, decision making, after-care and prevention. Women had a strong preference for normal vaginal birth, but willing to accept doctor’s decision for caesarean as they believed that it would protect the life of unborn child. Women perceived that caesarean was profitable to the hospital. Common mentioned side effects following caesarean were backache and pain at the surgical site. Conclusions: The understanding regarding caesarean section was adequate. Women had fears linked to caesarean such as pain, inability to work, weight gain, prolonged recovery and caesarean deliveries in subsequent pregnancies. Husbands and other family members as well as the doctors were the important decision makers, while the women themselves had little say in the matter. Obstetricians need to focus on alleviating concerns among pregnant women and their family members regarding caesarean section.